Semi -T- Small Submodules - Elewi, Alaa A. (Iraqi Journal of Science, 2021)
Let be a ring with identity and be a submodule of a left - module . A submodule of is called - small in denoted by , in case for any submodule of , implies . Submodule of is called semi -T- small in , denoted by , provided for submodule of , implies that . We studied this concept which is a generalization of the small submodules and obtained some related results